Impact of rhizobial inoculation and nitrogen utilization in plant growth promotion of maize (Zea mays L.) - RAMESH K. SINGH; NAMRATA MALIK; SURENDRA SINGH (Nusantara Bioscience, 2013)
Abstract. Singh RK, Malik N, Singh S. 2013. Impact of rhizobial inoculation and nitrogen utilization in plant growth promotion of maize (Zea mays L.). Nusantara Bioscience 5: 8-14. During the course of growing population demands, there has been an increasing interest in exploring the possibility of extending the beneficial interaction between cereals and plant growth promoting rhizobacteria (PGPR). Endophytes are a group of microorganism that resides mostly in the intercellular space of various parts of plants including cereals. Assessment of plant growth promoting properties of the five-rhizobial strains belonging to ? subclass i.e. Rhizobium leguminosarum bv. phaseoli RRE6 and R. undicola RRE36 and those belonging to ? subclass i.e. Burkholderia cepacia (RRE3, RRE5, RRE25) was done by growing maize plants inoculated with these strains. Inoculated maize plants showed a significant increase in plant height, root length, shoot and root dry weight over uninoculated control. R. leguminosarum bv. phaseoli RRE6 and B. cepacia RRE5 among the ? and ?-subclass representatives respectively, gave the best inoculation response. Effect of nitrate supplementation upon maize-RRE6 and RRE5 association was also studied and a significant increase in all the growth parameters and colonization ability was recorded when nitrate was present as a supplement over uninoculated control and maize-RRE6 and RRE5 in absence of external nitrate.